Norwegian Gas Sales and the Impacts on European CO2 Emissions - Elin Berg; Pål Boug; Snorre Kverndokk (Statistics Norway, Research Department, 1997)
This paper studies the impacts on Western European CO2 emissions of a reduction in Norwegian gas sales. The impacts are due to changes in energy demand and energy supply, but environmental and political regulations also play an important role. The gas supply model DYNOPOLY is used to analyse the effects on Russian and Algerian gas exports of a reduction in Norwegian gas supply. The effects on the demand side and the effects of committing to CO2 targets are analysed using the energy demand model SEEM. If the Western European countries commit to keeping their announced CO2 emissions targets, regardless of the costs associated with this, a reduction in Norwegian gas sales will have no impact on emissions. However, the consumption of oil and coal will increase slightly, while total energy consumption will go down. A reduction in Norwegian gas sales also seems to have only minor impacts on the CO2 emissions from Western Europe in the situation where no emissions regulations are considered.
Keywords: D92; L13; Q31; Q38; 330; Gas Sales; Energy Consumption; CO2 Emissions; Environmental Regulations.